Nutrient uptake and removal by runner peanut cultivars of different maturity groups - Cordeiro, Carlos Felipe dos Santos [UNESP]; Galdi, Leonardo Vesco; Echer, Fábio Rafael (Revista Brasileira de Ciencia do Solo, 2025)
Modern runner-type peanut cultivars have high yield potential, but little is still known about the dynamics of nutrient uptake by these cultivars and whether nutrient uptake differs between maturity groups. This study evaluated the growth, nutrient uptake, and nutrient removal of runner-type peanut cultivars with early and late maturity. The study was conducted in the field in the 2021/2022 season, in a sandy soil environment in southeastern Brazil. Treatments consisted of runner-type peanut cultivars (early and late maturity) and the phenological stage of sampling (V4/V5, R2/R3, R4, R5, R6, R7, and R8). Average pod yields were 4.0 and 5.9 Mg ha-1 for the early and late-maturity cultivars, respectively. Uptake of P, Cu, and Zn was linearly increased until stage R8. Nitrogen uptake continued until stage R7 for the early-maturity cultivars and stage R8 for the late-maturity cultivar. Potassium and B uptake did not increase after stages R5 and R6, respectively. For all other nutrients, maximum uptake occurred between stages R3 and R7. Leaf contents of all nutrients were within the sufficiency range, except Fe, which was higher than needed. Maximum macronutrient uptake (late-maturity cultivar) rates were 300, 28, 215, 76, 31, and 19 kg ha-1 for N, P, K, Ca, Mg, and S, respectively, and the maximum micronutrient uptake rates were 2350, 95, 391, 659, and 414 g ha-1 for Fe, Cu, Zn, Mn, and B, respectively. Maximum macronutrient removal rates were 210, 20, 48, 15, 7, and 12 kg ha-1 for N, P, K, Ca, Mg, and S, respectively, and the maximum micronutrient removal rates were 967, 59, 236, 153, and 136 g ha-1 for Fe, Cu, Zn, Mn, and B, respectively. Late-maturity cultivar had higher biomass production and greater uptake of all nutrients except K and Fe. The uptake of K and Fe was the same for both maturity groups.
Keywords: macronutrients; micronutrients; nutrient dynamics; plant nutrition; sandy soil